2022
DOI: 10.1371/journal.pgph.0000219
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of COVID-19-related service disruptions on TB incidence and deaths in Indonesia, Kyrgyzstan, Malawi, Mozambique, and Peru: Implications for national TB responses

Abstract: Initial global-level estimates reported in June 2020 by the World Health Organization suggested that levels of disruption to TB service delivery could be as high as 25%-50% and result in an additional 6·3 million cases of tuberculosis (TB) and an additional 1·4 million TB-related deaths attributable to COVID-19 between 2020 and 2025. Quarterly epidemiological estimates and programmatic TB data capturing disruption levels to each TB service were collected by National TB Programmes in Indonesia, Kyrgyzstan, Mala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 14 publications
(21 reference statements)
1
9
0
Order By: Relevance
“…These findings complement other studies in Malawi that have found changes in single programmes like HIV, TB and neonatal care, or examined changes in a subset of health facilities [ 4 6 , 16 19 ]. The overall picture that emerges does not match the worst-case scenarios considered at the outset of the pandemic, in which the most key services were reduced to very low levels [ 33 35 ].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings complement other studies in Malawi that have found changes in single programmes like HIV, TB and neonatal care, or examined changes in a subset of health facilities [ 4 6 , 16 19 ]. The overall picture that emerges does not match the worst-case scenarios considered at the outset of the pandemic, in which the most key services were reduced to very low levels [ 33 35 ].…”
Section: Discussionsupporting
confidence: 82%
“…Retrospective evaluations have since found that disruptions to healthcare services did occur, especially in low-income and middle-income countries (LMICs) in Africa, South-East Asia and Eastern Mediterranean Regions [ 1 3 , 7 15 ], including Malawi [ 4 6 , 16 19 ], which is a low-income country in sub-Saharan Africa with a fragile healthcare system [ 20 ]. These studies have described disruptions to services relating to HIV, TB, routine immunisation, maternal and child health care, and outpatient visits (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, after controlling for previously identified associated factors, the COVID-19 pandemic did not have a statistically significant effect on patient, doctor delay, or treatment delay. We observed that this may be related to the overall lower power of the data collected during the pandemic compared to pre-pandemic, as COVID-19 disruptions to the Indonesian health system were reported by several studies [ 51 , 52 ]. We also could not establish the associations between the delays and previously identified factors, such as age, educational level, and insurance status [ 50 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 89%
“…A recent study in Italy showed that, despite efforts to maintain TB services, there was a sudden increase in service disruption during the COVID-19 outbreak (9). These service interruptions will likely have long-term consequences on TB burden, and a modeling study predicts a 4% increase in TB deaths worldwide and 5.7% excess deaths in India over the period from 2020 to 2025 due to the COVID-19 lockdown (10)(11)(12). Studies using national data to assess the impact of the COVID-19 pandemic on TB services have not previously been conducted in any Central Asian country.…”
Section: Introductionmentioning
confidence: 99%